Audit Committee Characteristics and Restatements - Abbott, Lawrence J.; Parker, Susan; Peters, Gary F. (Auditing : a journal of practice and theory, 2004)
This study addresses the impact of certain audit committee characteristics identified by the Blue Ribbon Committee on Improving the Effectiveness of Corporate Audit Committees (BRC) on the likelihood of financial restatement. We examine 88 restatements of annual results (without allegations of fraud) in the period 1991–1999, together with a matched pairs control group of firms of similar size, exchange listing, industry and auditor type. We find that the independence and activity level (our proxy for audit committee diligence) of the audit committee exhibit a significant and negative association with the occurrence of restatement. We also document a significant negative association between an audit committee that includes at least one member with financial expertise and restatement. To test the robustness of the results we also consider a sample of 44 fraud and no-fraud firms and arrive at largely similar findings. Our results underscore the importance of the BRC's recommendations as a means of strengthening the monitoring and oversight role that the audit committee plays in the financial reporting process.